Fractional zeolite and method for producing the same

By using a combination method of structure-induced substances and surfactants in the zeolite synthesis process, the problem of uneven morphology of graded zeolites in the prior art is solved, and the synthesis of uniform morphology and improved activity is achieved, thereby improving the catalysis of zeolites Performance and application efficiency.

CN112714750BActive Publication Date: 2025-02-25SK INNOVATION CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN201980061038.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2018-09-21
Filing Date
2019-09-20
Publication Date
2025-02-25
Estimated Expiration
2039-09-20

AI Technical Summary

Technical Problem

It is difficult to effectively synthesize a fractionated zeolite with a uniform morphology in the prior art, especially when multiple surfactants are used simultaneously, problems of crystallization instability and uneven morphology are prone to occur.

Method used

By preparing a first mixed solution including a structure-induced substance, an alumina precursor and a pH adjuster, and adding silica precursor and surfactant thereon, a third mixed solution is formed, followed by drying and heat treatment, To synthesize a fractionated zeolite with a uniform morphology.

Benefits of technology

The synthesis of fractionated zeolites with uniform morphology and improved activity without increasing process complexity and cost is achieved, improving the catalytic performance and application efficiency of the zeolite.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN112714750B_ABST
    Figure CN112714750B_ABST
Patent Text Reader

Abstract

The invention relates to a method for producing a graded zeolite, wherein the method comprises: producing a first mixed solution comprising a structure inducing substance, an alumina precursor and a pH adjuster; adding a silica precursor to the first mixed solution to produce a second mixed solution; producing an aqueous solution comprising a surfactant; adding the aqueous solution to the second mixed solution to produce a third mixed solution; and drying and heat treating the third mixed solution. According to the present invention, a graded zeolite having a uniform morphology can be produced, thereby providing a graded zeolite having improved activity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a graded zeolite and a method for producing the same. Background Art

[0002] Zeolite is a microporous crystalline aluminosilicate with a general framework structure of silicon and aluminum atoms coordinated into tetrahedra by shared oxygen atoms. Zeolite is used in many applications due to its inherent porosity, wide water accessibility, low cost and high efficiency.

[0003] The main uses of zeolites are as catalysts in petrochemical decomposition, for separation and removal of gases and solvents, and in ion-exchange applications in water softening, purification, heavy metal removal, and nuclear waste treatment. This is because the exchangeable ions (sodium, calcium, and potassium ions) in zeolites are relatively harmless. Further, in other application areas such as aquaculture, agriculture, and animal husbandry, they are used for filtering, deodorizing, and drying. For example, clinoptilolite (a typical natural zeolite) has been widely studied as an ion exchanger and can also be used commercially in the treatment of industrial and municipal wastewaters to reduce the concentration of ammonia.

[0004] Zeolites are generally microporous materials, but recently, mesoporous zeolites, i.e., zeolites with medium-sized pores of 2 nm or more, have been studied. The development of mesoporous zeolites has made it possible to apply molecular materials that were previously limited, such as adsorption and separation of molecules with pores larger than those of microporous materials, and catalytic conversion reactions.

[0005] In order to add mesopores to zeolites with micropores, methods of melting from alkaline solutions are used, but these methods are not only difficult to obtain reproducible samples, but also require additional processes. In addition, the existing zeolites are cut, which reduces the overall yield and reduces economic efficiency.

[0006] On the one hand, surfactants capable of being introduced into the mesopores may be additionally added during the synthesis of zeolite. However, when two or more surfactants are used simultaneously, there is a problem that the different surfactants cannot grow crystals according to their respective functions and cannot form crystals due to mutual interference caused by the mixing. Summary of the invention

[0007] (Issues to be solved)

[0008] The present invention aims to solve the above-mentioned problems and provides a graded zeolite having a uniform morphology even when two or more surfactants are used simultaneously, and a method for producing the same.

[0009] (Methods to solve the problem)

[0010] According to one aspect of the present invention, a method for producing graded zeolite is provided, wherein the method for producing graded zeolite comprises: a step of producing a first mixed solution comprising a structure inducing substance, an alumina precursor and a pH regulator; a step of adding a silica precursor to the first mixed solution to produce a second mixed solution; a step of producing an aqueous solution comprising a surfactant; a step of adding the aqueous solution to the second mixed solution to produce a third mixed solution; and a step of drying and heat treating the third mixed solution.

[0011] The structure inducing substance may be included in a molar ratio of 1 / 120 to 1 / 50 relative to the amount of silicon dioxide.

[0012] The surfactant is added at a molar ratio of 1 / 200 to 1 / 50 relative to the amount of silica.

[0013] The concentration of the surfactant in the aqueous solution may be 77 mmol / L to 360 mmol / L.

[0014] The structure inducing substance may be at least one selected from the group consisting of tetramethylammonium bromide, tetramethylammonium chloride, tetramethylammonium hydroxide, tetraethylammonium bromide, tetraethylammonium chloride, tetraethylammonium hydroxide, tetraethylammonium tetrafluoroborate, hexamethonium chloride, and hexamethonium bromide.

[0015] The surfactant may be at least one selected from the group consisting of cetyltrimethylammonium bromide, cetyltrimethylammonium chloride, and cetylpyridinium chloride.

[0016] The step of preparing the third mixed solution is to add an aqueous solution including a surfactant to the second mixed solution in a dropwise manner.

[0017] The method for producing the graded zeolite may be performed without including seeds.

[0018] According to another aspect of the present invention, there is provided a graded zeolite, wherein the graded zeolite is produced by the above-mentioned production method.

[0019] (Effects of the Invention)

[0020] According to the present invention, a graded zeolite having a uniform morphology can be produced, and thereby a graded zeolite having improved activity can be provided. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1The figures are scanning electron microscope (SEM) photographs of zeolites according to Example 1 of the present invention (a), Example 2 (b), Comparative Example 1 (c), and Comparative Example 2 (d).

[0022] Figure 2 Graphs 1 and 2 show the particle size distribution of zeolites according to examples and comparative examples of the present invention.

[0023] Figure 3 FIG. 1 is an X-ray diffraction (XRD) diagram of zeolites according to examples and comparative examples of the present invention.

[0024] Best Mode for Carrying Out the Invention

[0025] Hereinafter, preferred embodiments of the present invention will be described with reference to various embodiments. However, the embodiments of the present invention can be modified in various other forms, and the scope of the present invention is not limited to the embodiments described below.

[0026] The present invention relates to a graded zeolite and a method for producing the same.

[0027] Zeolites, especially ZSM-48, have linear channels with 10-membered rings that are not interconnected and have ideal dimensions. ZSM-48 is a material including micropores, but when mesopores are added, the diffusion rate of the feed material is increased to improve the catalyst performance, and the feed with a larger molecular size can also be processed.

[0028] The present inventors have completed the present invention by focusing on the effects of the stabilization of the surfactant and the addition rate of the surfactant on the morphology when a structure inducing substance and a surfactant are used to add mesopores to such a zeolite having micropores.

[0029] According to one aspect of the present invention, there is provided a method for producing graded zeolite, comprising: a step of producing a first mixed solution comprising a structure inducing substance, an alumina precursor and a pH regulator; a step of adding a silica precursor to the first mixed solution to produce a second mixed solution; a step of producing an aqueous solution comprising a surfactant; a step of adding the aqueous solution to the second mixed solution to produce a third mixed solution; and a step of drying and heat treating the third mixed solution.

[0030] First, a first mixed solution including a structure inducing substance, an aluminum oxide precursor, and a pH adjuster is prepared. The structure inducing substance, the aluminum oxide precursor, and the pH adjuster may be mixed sequentially or simultaneously to prepare the mixed solution, and water, for example, may be used as a solvent.

[0031] Preferably, the structure inducing substance has a carbon number below C10 and an ammonium functional group, for example, at least one selected from the group consisting of tetramethylammonium bromide, tetramethylammonium chloride, tetramethylammonium hydroxide, tetraethylammonium bromide, tetraethylammonium chloride, tetraethylammonium hydroxide and tetraethylammonium tetrafluoroborate, hexamethonium chloride and hexamethonium bromide.

[0032] The structure inducing substance is added at a molar ratio of 1 / 120 to 1 / 50 relative to the amount of silica, preferably 1 / 100 to 1 / 50, and more preferably 1 / 80 to 1 / 50. When the molar ratio of the structure inducing substance relative to the amount of silica is less than 1 / 120, the molar ratio of the substance that can induce the structure is small, thereby generating the remaining silica that does not participate in the formation of the zeolite structure, thereby forming silica crystals, etc., which can reduce the overall purity and the overall acquisition rate. On the contrary, excessive structure inducing substances form other structures between structure inducing substances, thereby forming impurities different from the zeolite structure to be synthesized, or forming different morphologies even if the same structure is formed, thereby reducing the purity. Therefore, it is preferably not more than 1 / 50.

[0033] The aluminum oxide precursor used in the present invention is not particularly limited, and for example, one or more selected from the group consisting of sodium aluminate, sodium aluminum sulfate, and aluminum can be used.

[0034] The amount of the alumina precursor used can be determined according to the molar ratio of silica to alumina of the desired zeolite. For example, the alumina precursor can be used to make the silica to alumina molar ratio (SiO2 / Al2O3 Mole Ratio) in the range of 5 to 50, preferably in the range of 10 to 40, more preferably in the range of 15 to 30, but not limited thereto.

[0035] As the pH adjuster, a basic substance such as lithium hydroxide, sodium hydroxide, potassium hydroxide, rubidium hydroxide, cesium hydroxide, or ammonium hydroxide can be used.

[0036] The pH adjusting agent may be added to make the pH of the first mixed solution be 12 or more, preferably in the range of 12 to 14. When the pH is less than 12, the silica precursor cannot be well dissociated and does not participate in the reaction, so that impurities that may act on the sample and become silica crystals are generated during the crystallization process. Accordingly, specifically, the pH adjusting agent is added at a molar ratio of 0.1 to 0.4, preferably 0.1 to 0.3, and more preferably 0.15 to 0.25 relative to the amount of silica.

[0037] Next, a silica precursor is added to the first mixed solution to prepare a second mixed solution. The silica precursor is added to the mixed solution including the structure inducing substance, the alumina precursor and the pH adjuster, so that the zeolite basic structure can be formed.

[0038] The silica precursor may be, for example, one or more selected from the group consisting of silica, precipitated silica, colloidal silica, sodium silicate, tetramethyl orthosilicate, tetraethyl orthosilicate, borosilicate, and fluorosilicate, and is not particularly limited.

[0039] Preferably, the silica precursor is added to the water included in the entire composition for zeolite synthesis, that is, the third mixed solution described later, so that the silica-to-water mole ratio is in the range of 0.01 to 0.1. The silica-to-water mole ratio is preferably 0.03 to 0.08, and more preferably 0.05 to 0.07.

[0040] Next, an aqueous solution including a surfactant is added to the second mixed solution to prepare a third mixed solution. The aqueous solution including a surfactant is added so that the surfactant can be introduced into the mesopores in a graded manner.

[0041] First, an aqueous solution including a surfactant is manufactured. At this time, in the case of a surfactant in the form of an aqueous solution, it is diluted in water and stirred to be uniformly dispersed, and the surfactant in the form of a powder is stirred into a uniform solution in the form of an aqueous solution. The concentration of the surfactant in the aqueous solution can be 77mmol / L to 360mmol / L, preferably, 77mmol / L to 230mmol / L. When it is above 360mmol / L, the surfactant is not sufficiently stabilized and its effect is minimal. When it is below 77mmol / L, a relatively large amount of water enters the surfactant, so the amount of water in the second mixed solution required to form a gel (Gel) decreases, resulting in reduced uniformity.

[0042] On the one hand, preferably, the surfactant has a carbon number of C11 or more and an ammonium functional group, for example, at least one selected from the group consisting of cetyltrimethylammonium bromide, cetyltrimethylammonium chloride and cetylpyridinium chloride.

[0043] In the process of adding the aqueous solution including the surfactant to the second mixed solution, the surfactant is added at a molar ratio of 1 / 200 to 1 / 50 relative to the amount of silica, preferably 1 / 150 to 1 / 50, and more preferably 1 / 120 to 1 / 60. When the surfactant exceeds 1 / 50 in molar ratio relative to the amount of silica, an amorphous substance of the silica component is generated together, which may cause a problem of reducing the crystallinity and uniformity of EU-2 itself. On the one hand, when the amount of the surfactant is less than 1 / 200, the ions of the surfactant cannot be effectively bound to the periphery of the seed, so there is a problem that the mesopores cannot be effectively formed.

[0044] As described above, when a structure-inducing substance and a surfactant are added to produce a zeolite having micropores and mesopores, the surfactant is added after diluting and stirring the aqueous solution and stabilizing it, thereby obtaining a zeolite having a more uniform morphology.

[0045] On the one hand, in order to produce a zeolite with a uniform morphology, it is preferred to add the aqueous solution including the surfactant to the second mixed solution dropwise, wherein, for example, the dropwise manner means a method of slowly adding the surfactant using a dropper or a burette, and the addition can be performed at a speed of less than 50 cc / min, such as 1 to 40 cc / min, 4 to 30 cc / min, 6 to 20 cc / min, etc.

[0046] When synthesized by the method described above, the surfactant is effectively close to the gel, which is conducive to the production of a uniform morphology. This is because under the corresponding synthesis conditions, the negative charge on the surface of the silica gel interacts with the positive charge as the surface charge of the surfactant, and the silica gel and the surfactant are added dropwise so that the silica gel and the surfactant interact more effectively, thereby obtaining a uniform morphology. On the contrary, when adding in a one-pot method, an excessive amount of surfactant is added at one time, so there is a problem of obtaining an uneven morphology.

[0047] In the step of drying and heat treating the third mixed solution, the heat treatment may be performed at a reaction temperature of 140-190° C., preferably 150-180° C., and more preferably 160-180° C. Below 140° C., the crystallization of the graded zeolite is poor, thus reducing or not forming crystallinity, and above 190° C., an over-reaction occurs, thereby forming quartz etc. as impurities and the surfactant may be decomposed at high temperature.

[0048] The heat treatment time may be longer than 48 hours, but increasing the synthesis time to improve crystallinity may have the side effect of generating quartz. Therefore, the heat treatment is preferably performed for 48-50 hours.

[0049] On the one hand, the manufacturing method of the graded zeolite according to one aspect of the present invention can be performed without seeds. Generally, the synthesis of mesoporous zeolite is not uniform without using seeds, so seeds are used. However, the manufacturing method according to the present invention can stably synthesize zeolite including micropores and mesopores without using seeds.

[0050] According to another aspect of the present invention, there is provided a classified zeolite produced by the production method. The zeolite produced by the production method according to the present invention has a BET surface area of ​​260 g / ㎡ or more and a mesopore volume of 0.20 g / cm 3 Above and PSD is less than 6μm in size. DETAILED DESCRIPTION

[0051] The present invention will be described in more detail below by way of examples. The following examples are provided to describe the present invention in more detail, and therefore, the present invention is not limited thereto.

[0052] <Example 1>

[0053] 1.37 g of hexamethonium chloride as a mold material, 0.46 g of sodium aluminate as an alumina raw material, and 2.49 g of sodium hydroxide (NaOH) were dissolved in 46 g of deionized water (DI Water) to prepare a mixed solution, and 48.16 g of Ludox-HS40 as a silica raw material was added to the mixed solution.

[0054] After 30 g of water was added to 4.36 g of cetyltrimethylammonium chloride (CTAC) and stirred, it was added to the solution from a One-pot while the temperature was maintained at room temperature.

[0055] The final mixture was added to a hydrothermal synthesis reactor coated with polytetrafluoroethylene material, and reacted at 160°C for 2 days (48 hours) to obtain a zeolite material. The zeolite material was fully washed with distilled water, dried at 60°C for 12 hours, and calcined at 550°C for 5 hours, thereby producing a graded zeolite having both micropores and mesopores and CTAC without organic surfactant.

[0056] <Example 2>

[0057] 1.37 g of hexamethylammonium chloride as a mold material, 0.46 g of sodium aluminate as an alumina raw material, and 2.49 g of sodium hydroxide (NaOH) were dissolved in 46 g of deionized water (DI Water) to prepare a mixed solution.

[0058] 48.16 g of Ludox-HS40 as a silica raw material was added to the solution. 30 g of water was added to 4.36 g of hexadecyltrimethylammonium chloride (CTAC) and stirred, and then added to the solution dropwise, i.e., by titrating at a rate of 20 cc / min using a dropper. At this time, the temperature was maintained at room temperature.

[0059] The final mixed solution was added to a hydrothermal synthesis reactor coated with polytetrafluoroethylene material, and reacted at 160°C for 2 days (48 hours) to obtain a zeolite material. After the zeolite was fully washed with distilled water, it was dried at 60°C for 12 hours and calcined at 550°C for 5 hours, thereby producing a graded zeolite (HEU2-Na) having both micropores and mesopores and removing CTAC as an organic surfactant.

[0060] <Comparative Example 1>

[0061] 1.37 g of hexamethonium chloride as a mold material, 0.46 g of sodium aluminate as an alumina raw material, and 2.49 g of sodium hydroxide (NaOH) were dissolved in 76 g of deionized water (DI Water) to prepare a mixed solution, and 48.16 g of Ludox-HS40 as a silica raw material was added to the solution.

[0062] 4.36 g of hexadecyltrimethylammonium chloride (CTAC) was added dropwise to the solution. At this time, the temperature was maintained at room temperature. The final mixture was added to a hydrothermal synthesis reactor coated with polytetrafluoroethylene material, and reacted at 160°C for 2 days (48 hours) to obtain a zeolite material. After that, it was fully washed with distilled water, dried at 60°C for 12 hours and calcined at 550°C for 5 hours, thereby manufacturing a graded zeolite with both micropores and mesopores and CTAC with organic surfactant removed.

[0063] <Comparative Example 2>

[0064] 1.37 g of hexamethonium chloride as a mold material, 0.46 g of sodium aluminate as an alumina raw material, and 2.49 g of sodium hydroxide (NaOH) were dissolved in 76 g of deionized water (DI Water) to prepare a mixed solution, and 48.16 g of Ludox-HS40 as a silica raw material was added to the solution.

[0065] 4.36 g of cetyltrimethylammonium chloride (CTAC) was added to the solution from One-pot, while the temperature was maintained at room temperature.

[0066] The final mixed solution was added to a hydrothermal synthesis reactor coated with polytetrafluoroethylene material, and reacted at 160°C for 2 days (48 hours) to obtain a zeolite material. After that, it was fully washed with distilled water, dried at 60°C for 12 hours and calcined at 550°C for 5 hours, thereby producing a graded zeolite with both micropores and mesopores and CTAC without organic surfactant.

[0067] The specific surface area (S) of the zeolites according to the embodiments and comparative examples is BET (BET surface area, BET surface area), S micro (micropore area), S ext (external surface area), pore volume (V total (total volume), V meso The mesopore volume and particle size are shown in Table 1.

[0068]

Table 1

[0069]

[0070] Referring to Table 1, it can be confirmed that the V of Comparative Examples 1 and 2 which do not satisfy the concentration conditions of the present invention meso The properties are poor, while the macromolecules of Examples 1 and 2 can approach V meso It is greatly developed. Further, when added to Example 2 in a dropwise manner, it can be seen that the particle size is also very small, which has a positive impact on the housing type.

[0071] As described above, the embodiments of the present invention are described in detail, but the scope of the present invention is not limited thereto, and those skilled in the art can understand that various modifications and variations can be made without departing from the technical concept of the present invention described in the claims.

Claims

1. A method for producing a graded zeolite, characterized in that: The method for producing the graded zeolite comprises: The step of preparing a first mixed solution including a structure inducing substance, an aluminum oxide precursor and a pH adjuster; A step of adding a silicon dioxide precursor to the first mixed solution to prepare a second mixed solution; A step of preparing an aqueous solution consisting of a surfactant and water; adding the aqueous solution consisting of a surfactant and water to the second mixed solution dropwise to prepare a third mixed solution; and The step of heat treating and drying the third mixed solution, wherein the third mixed solution is heat treated at a reaction temperature of 140-190° C. for 48-50 hours, The surfactant is at least one selected from the group consisting of cetyltrimethylammonium bromide, cetyltrimethylammonium chloride and cetylpyridinium chloride.

2. The method for producing a classified zeolite according to claim 1, wherein: The structure inducing substance is added at a molar ratio of 1 / 120 to 1 / 50 relative to the amount of silicon dioxide.

3. The method for producing a classified zeolite according to claim 1, wherein: The surfactant is added at a molar ratio of 1 / 200 to 1 / 50 relative to the amount of silica.

4. The method for producing a classified zeolite according to claim 1, wherein: The structure inducing substance is at least one selected from the group consisting of tetramethylammonium bromide, tetramethylammonium chloride, tetramethylammonium hydroxide, tetraethylammonium bromide, tetraethylammonium chloride, tetraethylammonium hydroxide, tetraethylammonium tetrafluoroborate, hexamethonium chloride and hexamethonium bromide.

5. The method for producing a classified zeolite according to claim 1, wherein: No seeds are used.

6. A graded zeolite, wherein: The graded zeolite is produced by the method for producing a graded zeolite according to any one of claims 1 to 5.

Citation Information

Patent Citations

  • Rapid crystallization method for Y type molecular sieve

    CN101481120A

  • ZSM-5 molecular sieve with high specific surface area and preparation method thereof

    CN103848440A